Kajian Intertekstual Novel Dilan Karya Pidi Baiq dengan Novel Milea Karya Pidi Baiq - Ani Marliana; Idawati Sintiawati; Mimin Sahmini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Literary works are the media used by the author in conveying ideas, experiences to be conveyed to the reader. In addition, literary works can also be found in the intertextual relationship between one literary work with other literary works. The purpose of this study is to know how the intertextual relationship between the novel "Dilan he is Dilanku 1990", "Dilan he is Dilanku 1991," and novel "Milea sounds from Dilan" by Pidi Baiq, where the three novels have intertextual relationships in the theme, the background, the plot, the character, the style, the point of view, and the message. Based on the results of the study, there is an intertextual relationship between the novel "Dilan he is Dilanku 1990," novel "Dilan he is Dilanku 1991," and the novel "Milea Dilan hearts of heart," in terms of themes, viewpoints, and backgrounds used in the three novels. The equations of the three novels are the theme of romance. The method used in this research is a descriptive method that is the method that describes the contents of the three novels reviewed.